الفكــر التـــربـــوي عنـــد ابو يوسف يعقوب بن اسحق الكنــــدي ( دراسة نظرية ) (Journal Of Educational and Psychological Researches, 2014)
Every era characterizes with its thought and life philosophy , where Muslims left behind them educational and intellectual heritage we should proud of it because it reflects the image of past and lights the way of present and future path where we should make use of it to fit with our statuesque and contemporary issues because we don’t know about it but little as result of ignorance or imitation of the western culture.       It’s wrong to regard heritage from the past but aphasia of Islamic and Arab genies that its roots tracing back to past and extending to future .      Islamic Arab educational thought regards one of the richest in the field of science and knowledge ,where the study of it makes the reader having the lessons shedding his way for solving the present problems in the light of understanding the past because education is the daughter of long history and deeply experience .    One of the thinkers of educational thought is ALKindi where he appreciated the importance of learning and the teacher in the life of individual and nation mirroring the integration of Man physically and morally where school is asocial institution and an active tool by which the cultural changes and common national goals can be achieved ,so , he  puts his teaching and educational philosophy in an educational and directive framework and asserts that science has a great value where it is not an information but a method and away for having them and it is the main factor of senses the learning process .      So, the researcher has been chosen this philosopher because of his great role in reaching and deepen our educational and intellectual thought and to know what he adds to our educational system . The present study aims at recognizing the educational thought of AL-Kindi by knowing his selecting of the teacher , his characters , and the methods of teaching basing on the interaction between him and the student . The limits of this study include the teacher , his characters , methods of teaching and his educational thoughts . This study concludes whit that must be conditions for being a teacher such as : Loyalty in doing his duty , has the capacity of assessing things , the teacher should be away of arrogance , river stopping reading ( the so called now days the continuous learning ), has an information  about semantic and hovels ,has areole in educating minds ,ricking students with various information and helping in understanding what they have to learn .As for the curriculum it was “Quran” the basis of legitimize laws and identifying the rights and duties of human and the holly talks of the prophet Mohammed .      The conclusions of this study are :He regards the student is the core of educational process , helping him to reach perfection . directing him to be a man with educational and cultural thought helping in transferring the experiences and forming different social ideates and as for the girl he asserts that the source of the information of her is her freedom and to learn without a teacher because her primitive aptitude helps her to learn from her parents .